2013
DOI: 10.1111/eos.12054
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of tooth agenesis in patients with orofacial clefts

Abstract: Orofacial clefts are a common oral disorder associated with tooth agenesis. As information on the simultaneous absence of teeth can be an aid in treatment planning, a large sample of orofacial cleft patients was examined. The sample consisted of 910 patients with cleft lip and palate. Tooth agenesis was assessed on the basis of at least two panoramic radiographs and patient records. Third-molar agenesis was determined in 474 patients. Patterns of tooth agenesis were analysed using Tooth Agenesis Code (TAC) val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 17 publications
2
29
1
Order By: Relevance
“…A trend for more hypoplasia was also found for the CL only group (p=0.001). This finding is consistent with work by Hermus et al that found the rate of agenesis to be positively correlated with cleft severity, whereby the percent of agenesis was 13.5% in CL, 33.8% in CLA, and 52.4% in CLP (Hermus, van Wijk et al 2013). Another study found that dental anomalies are collectively more prevalent in the CLP group compared to other cleft types and controls (Howe, Cooper et al 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A trend for more hypoplasia was also found for the CL only group (p=0.001). This finding is consistent with work by Hermus et al that found the rate of agenesis to be positively correlated with cleft severity, whereby the percent of agenesis was 13.5% in CL, 33.8% in CLA, and 52.4% in CLP (Hermus, van Wijk et al 2013). Another study found that dental anomalies are collectively more prevalent in the CLP group compared to other cleft types and controls (Howe, Cooper et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…A recent study found the rate of dental agenesis to be 13.5% in CL, 33.8% in CLA, and 52.4% in CLP. The average rates of dental agenesis by dental arch in this population were found to be 35.1% in the maxilla and 11.5% in the mandible (Hermus, van Wijk et al 2013).…”
Section: Dental Agenesismentioning
confidence: 69%
“…By contrast, Shapira et al found a cleft side predominance for missing lateral incisors and second premolars in the maxillary and mandibular arch [ 42 ]. However, there is a positive correlation between hypodontia and severity of the cleft, with an increasing frequency of missing teeth as the severity of the cleft increases, resulting in more missing teeth in UCLP and BCLP patients with more teeth missing both inside and outside the cleft area [ 1 , 2 , 33 , 36 , 56 , 60 , 85 , 99 101 ]. For example, in UCLP patients the second upper premolar was missing in 11.8–52.6% [ 2 , 33 , 60 , 81 , 85 , 86 , 95 , 97 ], and in BCLP patients values of 21.6–68.4% [ 2 , 60 , 97 , 102 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing these findings to the general population, the control probands have similar frequencies of agenesis to that in the general population (0.6 -5.2%) but the case probands have a much higher incidence of agenesis than the general population (Bailit, 1975;Polder et al, 2004;Ranta et al, 1983). Hermus et al, 2013;Jordan et al, 1966;Ranta et al, 1983;Schroeder & Green, 1975). Previous studies have only looked at permanent teeth and no reports were found specifically for agenesis of primary teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Of these missing teeth the maxillary lateral incisor was the most common followed by the maxillary and mandibular second premolar respectively. They also examined the relationship of the extent of the cleft and agenesis and found that the prevalence of tooth agenesis was significantly associated with an increase in the cleft extent ranging from CL at 13.5% to CLP at 52.4% (Hermus, van Wijk, Tan, Kramer, & Ongkosuwito, 2013).…”
Section: Hypodontiamentioning
confidence: 99%